Use of Sweet Mango Leaves (Mangifera indica) To Reduce Germs Colonies on Cutlery (International Journal of Scientific Research and Management (IJSRM), 2023)
According to WHO, the global death rate due to diarrhea in 2002 was 1.8 million people. Global morbidity rates due to PBM (Community Based Diseases) are very difficult to estimate. Apart from diarrhea, there are more than 250 types of diseases caused by consuming unsafe food. This study aims to determine the difference in average germ numbers before and after using soap made from mango leaf powder. This research is an experimental study with a pre-post design to determine the ability of dishwashing soap made from sweet fragrant mango leaves to reduce germ colonies. The population and sample in this study were cutlery in the form of spoons, glasses and plates, each consisting of 5 samples. Examination of the samples was carried out before and after using dish soap. Data is collected from an observation sheet which contains the number of germ colonies in each sample examined. Data were analyzed using the paired t test. This research was conducted at the Microbiology Laboratory of the Integrated Health Polytechnic Laboratory of the Ministry of Health in Ternate. The results showed that the average germ number in the pre-test was 2454.44 ± 668.70, while in the post-test the average germ number was 1178.67 ± 249.61. The P value = 0.012 (< 0.05) indicates that there is a significant difference in the average number of germs before and after using soap made from mango leaf powder. The conclusion is that using soap made from mango leaf powder can significantly reduce the number of germs on the hands. This shows the potential of soap as an effective alternative in maintaining cleanliness and reducing the risk of spreading disease through hand contact.